Prediction performance of two stroke semi free piston diesel engine with dual piston system - Muhammad Fathallah, Aguk Zuhdi; Bimatara, Ian; Rosli, Abu Bakar (IOP Publishing, 2021)
The design of the semi-free piston two-stroke diesel engines has been successfully implemented. Before the engine is built, it is necessary to predict its performance. Prediction is done by using the simulation method. This method is considered the most effective because it does not fabricate the machine first. Modelling and simulation are done using application software. Simulation modelling covers all parts of the engine, namely the intake system, block, injection system, and then exhaust system. Engine performance predictions are based on speed variations as well as load variations. Validation is done with a conventional machine. The difference between the two engines lies in friction losses, where the free piston concept is to reduce friction losses. The simulation results are engine performance such as torque, power, bsfc, bmep, and combustion processes such as heat release, pressure, and ignition delay. The difference in the performance of the semi-free piston compared to a conventional engine with the same combustion chamber size. Prediction results state that the difference in performance is very significant.